THE POTENTIAL OF THE CROWDSOURCING AS A METHOD OF LINGUISTIC EXPERIMENT - M. V. Danilchuk (Вестник Кемеровского государственного университета, 2018)
The present research considers crowdsourcing as a method of linguistic experiment. The paper features an experiment with the following algorithm: 1) problem statement, 2) development, 3) and questionnaire testing. The paper includes recommendations on crowdsourcing project organization, as well as some issues of respondents’ motivation, questionnaire design, choice of crowdsourcing platform, data export, etc. The linguistic experiment made it possible to obtain data on the potential of the phonosemantic analysis in solving naming problems in marketing. The associations of the brand name designer matched those of the majority of the Internet pannellists. The experiment showed that crowdsourcing proves to be an available method within the network society. It gives an opportunity to receive objective data and demonstrates high research capabilities. The described procedure of the crowdsourcing project can be used in various linguistic experiments.